PENGARUH MEDIA PERMAINAN PROFIT-OPOLY TERHADAP PEMAHAMAN KONSEP SISWA PADA MATERI ARITMATIKA SOSIAL KELAS VII SMP - Yuni Suradi; Novi Susanti; Helni Indrayati (LPPM Institut Ahmad Dahlan Probolinggo, 2026)
The low level of conceptual understanding in social arithmetic material at SMP Muhammadiyah 26 jarai serves as the background for this study, which aims to determine the effect of the profit-opoly game media. This study employed a quantitative approach with a quasi-experimental method and a Pretest-Posttest Control Group Design. The participant involved students from class VII.A as the experimental group and class VII.C as the control group. The data were collected through test instrument that had been verified for validity. The findings of this study indicated that the average posttest score of the experimental class was 73.43, with an average conceptual understanding percentage of 77,13%, while the control class only reached an average score of 53.11 with a average conceptual understanding percentage of 58.77%. Based on the Independent Sample t-Test result, it was found that the equal variances assumed had a sig.(2-tailed) value 0,000 < 0.05, or it could also be seen from the value of = 3.998 > = 1.673. Therefore,it can be concluded that was rejected and was accepted, meaning that there was an effect of using the profit-opoly game media on student’s conceptual understanding in social arithmetic material.